Inhibitory effects of cassiae semen extract on the formation of 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) in model system - Yu, Di; Li, Youyou; Jiang, Donghua; Kong, Fanlei (Frontiers in Nutrition, 2024)
2-Amino-1-methyl-6-phenylimidazole [4,5-b] pyridine (PhIP), a heterocyclic amine (HAA), is found in meat products heated at high temperatures. To investigate the inhibitory effect of cassiae semen extract on PhIP formation within a model system and elucidate the inhibitory mechanism, an ultrasonic-assisted method with 70% ethanol was used to obtain cassiae semen extract, which was added to a model system (0.6 mmol of phenylalanine: creatinine, 1:1). PhIP was analyzed by LC-MS to determine inhibitory effect. The byproducts of the system and the mechanism of PhIP inhibition were verified by adding the extract to a model mixture of phenylacetaldehyde, phenylacetaldehyde and creatinine. The results indicated that PhIP production decreased as the concentration of cassiae semen extract increased, and the highest inhibition rate was 91.9%. Byproduct (E), with a masscharge ratio of m/z 199.9, was detected in the phenylalanine and creatinine model system but was not detected in the other systems. The cassiae semen extract may have reacted with phenylalanine to produce byproduct (E), which prevented the degradation of phenylalanine by the Strecker reaction to produce phenylacetaldehyde. Cassiae semen extract consumed phenylalanine, which is the precursor for PhIP, thus inhibiting the formation of phenylacetaldehyde and ultimately inhibiting PhIP formation.